On a link of rare earth-rare metal and gold-ore mineralizationwith fault-block tectonics of the Ukrainian shield. 2 - S. V. Nechaev; O.B. Gintov; S. V. Mychak (Геофизический журнал, 2019)
In the second article of the cycle «On a link of rare earth-rare metal and gold-ore mineralization with fault-block tectonics of the Ukrainian shield» [Nechaev et al., 2018] the internal structure, kinematics, age and metallogeny of the faults of the Gaivoron-Zavaliev section of the Pobuzhie mining region (PMR) of the Ukrainian shield (USh) have been considered. It is shown that the Gaivoron zone of faults with a width of up to 10 km consists of five shear zones of the latitudinal stretch, which make up the boundary between the Bug and Ros in megablocks of the USh. The kinematic shear zones are laid out as left shifts in the field of stresses σ1 45°, σ3 315°, σ2∟ (West-Ingulets stage). The youngest stage of their activization is the Subbotsk-Moshorin (σ1 312°, σ3 42°, σ2 ∟ — right shift). The actual Gaivoron shear zone is characterized by widespread lamprophyres with rare earth mineralization of La, Ce, Y, as well as increased content of Ti, Mn, Ba, Cr. Within the Khaschevat shear zone the Solomievsk deposit of aqueous phosphates with yttrium composition of ores and an iron-manganese deposit with a priority triad of Y, Yb, Ge, as well as Au are known among tectonites. The granitoids of the Ustye-Stavsk shear zone are characterized by an abnormally high monazite content. For the first time the internal structure and kinematics of the Zavaliev fault zone, the width of which is at least 4 km, is studied in detail. It is shown that it consists of two shear zones — the latitudinal actually Zavaliev and northeastern Peschanaya-Zhakchik. Both shear zones are observed in the Zavaliev graphite pit. The yformed, as the Gaivoron zone of faults, at the West-Ingulets stage, and the last phase of activіzation took place in the Subbotsk-Moshorin stage. The opinion that the Zavaliev structure is not a synclinal fold, as was supposed to be, but an intrafault lens of hydrothermalites-metasomatites. These include graphite-biotite gneisses and shales, ore and ore-free quartzites, calciphyres and skarnoids. In addition to the world’s reserves of graphite, elevated concentrations of gold, silver, platinum, and iridium are widely represented in the zone of faults (in zones of silicification and sulfidization of graphite-biotite gneisses).